PENGARUH RASIO SOLVABILITAS DAN RASIO PROFITABILITAS TERHADAP EARNING PER SHARE (Studi Empiris pada Perusahaan Otomotif dan Komponennya yang Terdaftar di BEI Periode 2014-2016) - Chyntia Melisa Pratiwi; Rodhiyah Rodhiyah (Jurnal Ilmu Administrasi Bisnis, 2018)
Earning Per Share is a benchmark used by investors to see if the company is operating well or not. The automotive sub-sector and its components listed on the IDX for the period 2014-2016 have Earning Per Share that mostly declined in 2015, but increased again in 2016. The purpose of research to determine the influence of solvency ratio (DAR and DER) and profitability ratio (ROA and ROE) to Earning Per Share. Data used are primary data from re-processed financial statements. Using purposive sampling with total samples that meets the criteria is 10 companies x 3 years resulting 30 panel data. The analysis method using linear regression and significance using SPSS ver. 21. Results and discussion: Solvency ratio: A few DAR is below the average and DER is mostly below the average. The lowest DAR value is 0.20 and the highest is 0.89. The lowest DER value is 0.20 and the highest is 8.26. Profitability ratio: ROA is mostly below the average and a few ROE below the average. The lowest ROA value is -0.13 and the highest is 0.24. The lowest ROE value is -1.24 and the highest is 0.37. DAR has no effect on EPS with significance (0.004<0.05) and regression coefficient (-1421,636). DER has no effect on EPS with significance (0,000<0.05) and regression coefficient (-307.897). ROA affects EPS with significance (0,000<0.05) and regression coefficient (4085,808). ROE affects EPS with significance (0,000<0.05) and regression coefficient (1783,304). Conclusion and suggestion: Solvency ratios and profitability ratios together have significant effect on Earning Per Share with Fcount>Ftable or (14,184)>(2,759) and significance (0,000<0,05). Companies should utilize loan funds more effectively to improve operations that increase corporate profits.